Polymorphism in Non‐Fullerene Acceptors Based on Indacenodithienothiophene. (13th May 2021) - Marina, Sara; Scaccabarozzi, Alberto D.; Gutierrez‐Fernandez, Edgar; Solano, Eduardo; Khirbat, Aditi; Ciammaruchi, Laura; Iturrospe, Amaia; Balzer, Alex; Yu, Liyang; Gabirondo, Elena; Monnier, Xavier; Sardon, Haritz; et al.
Abstract: Organic solar cells incorporating non‐fullerene acceptors (NFAs) have reached remarkable power conversion efficiencies of over 18%. Unlike fullerene derivatives, NFAs tend to crystallize from solutions, resulting in bulk heterojunctions that include a crystalline acceptor phase. This must be considered in any morphology‐function models. Here, it is confirmed that high‐performing solution‐processed indacenodithienothiophene‐based NFAs, i.e., ITIC and its derivatives ITIC‐M, ITIC‐2F, and ITIC‐Th, exhibit at least two crystalline forms. In addition to highly ordered polymorphs that form at high temperatures, NFAs arrange into a low‐temperature metastable phase that is readily promoted via solution processing and leads to the highest device efficiencies. Intriguingly, the low‐temperature forms seem to feature a continuous network that favors charge transport despite of a poorly order along the π–π stacking direction. As the optical absorption of the structurally more disordered low‐temperature phase can surpass that of the more ordered polymorphs while displaying comparable—or even higher—charge transport properties, it is argued that such a packing structure is an important feature for reaching highest device efficiencies, thus, providing guidelines for future materials design and crystal engineering activities. Abstract : Non‐fullerene acceptors used in organic solar cells often crystallize when they are solution processsed. ITIC and its derivatives ITIC‐M, ITIC‐2F, and ITIC‐Th, exhibit various polymorphs, including a metastable form that is readily promoted via solution processing and leads to the highest device efficiencies despite exhibiting poor order along the π–π stacking direction.